Burial and Memorial in Late Antiquity : Volume 1: Thematic Perspectives - Lavan, Luke, (Late Antique Archaeology., 2024)
Burial and Memorial explores funerary and commemorative archaeology, A.D. 284-650, across the late antique world, from Catalonia to Cappadocia. This first volume includes an overview of research, and papers exploring bioarchaeology, mortuary rituals, mausolea, and funerary landscapes. It considers the sacralisation of tombs, movements of relics, and the political significance of cemeteries. The fate of statue monuments is explored, as memorials for individuals. Authors also compare the spoliation or preservation of tombs to other buildings, and, finally, how the city itself, with its monuments, served as a place of collective memory, where meanings were long maintained.